2016
DOI: 10.1371/journal.pone.0162245
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Acute Myocardial and Skeletal Muscle Injury after Serial Transthoracic Shocks in Healthy Swine

Abstract: BackgroundPrevious serological studies have shown controversial results whether defibrillation or cardioversion can cause myocardial injury. Cardiovascular Magnetic Resonance (CMR) can be used to detect myocardial edema, hyperemia and capillary leak as features of acute myocardial injury. The aim of this study was to assess for myocardial and skeletal muscle injury in swine following transthoracic shocks.MethodsSeventeen anaesthetized swine were examined, with 11 undergoing five synchronized transthoracic shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Current defibrillators deliver biphasic electrical shocks, which are considered safer than monophasic electrical shocks for the myocardium . However, in a recent study—also in swine—synchronized biphasic electrical shocks delivered during spontaneous circulation (five 200‐J shocks in 5 minutes) were shown by cardiac magnetic resonance and histology to produce myocardial injury along the path of the electrical shock consistent with cell electroporation and capillary leakage leading to tissue edema . Functionally, there was reduction in left ventricular volumes indicative of diastolic dysfunction, an effect that we had previously reported after repetitive monophasic electrical shocks in an isolated rat heart model of VF .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Current defibrillators deliver biphasic electrical shocks, which are considered safer than monophasic electrical shocks for the myocardium . However, in a recent study—also in swine—synchronized biphasic electrical shocks delivered during spontaneous circulation (five 200‐J shocks in 5 minutes) were shown by cardiac magnetic resonance and histology to produce myocardial injury along the path of the electrical shock consistent with cell electroporation and capillary leakage leading to tissue edema . Functionally, there was reduction in left ventricular volumes indicative of diastolic dysfunction, an effect that we had previously reported after repetitive monophasic electrical shocks in an isolated rat heart model of VF .…”
Section: Discussionmentioning
confidence: 72%
“…12,13 However, in a recent study-also in swine-synchronized biphasic electrical shocks delivered during spontaneous circulation (five 200-J shocks in 5 minutes) were shown by cardiac magnetic resonance and histology to produce myocardial injury along the path of the electrical shock consistent with cell electroporation and capillary leakage leading to tissue edema. 42 Functionally, there was reduction in left ventricular volumes indicative of diastolic dysfunction, an effect that we had previously reported after repetitive monophasic electrical shocks in an isolated rat heart model of VF. 43 Our data suggest that shock burden could have been detrimental to the myocardium given its inverse relationship with both left ventricular function (modest association) and survival (weak association).…”
Section: Shock Burdenmentioning
confidence: 64%
“… 31 , 32 A previous study in swine showed that electrical shocks delivered during spontaneous circulation produced myocardial injury with functional reduction in left ventricular volume. 33 Histological analysis of these hearts revealed findings consistent with cell electroporation and capillary leakage, leading to tissue edema. A previous study in isolated rat hearts showed that repetitive monophasic shocks also resulted in decreased left ventricular volume and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 79%
“…Accordingly, step-wise global deceleration of early diastolic strain across the breathing maneuvers was observed, and this was associated with increased T2 burden. Edema is also linked with ventricular stiffness and when myocardial edema aggravates, the rise of interstitial pressure reduces ventricular chamber compliance ( 34 , 35 ). While T2 is not often chronically elevated, edema at the time of CO 2 challenges may predispose cardiac patients to diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%